How does the extension of existing transport infrastructure affect land value? A case study of the Tyne and Wear Light Transit Metro system. (January 2022) - Pearson, Jonathan; Muldoon-Smith, Kevin; Liu, Henry; Robson, Simon
Abstract: This paper seeks to investigate the timing of land value uplift associated with an extension to an existing light rail transport system. It seeks to understand the amount of land value increase on residential properties at different stages of the infrastructure delivery process of the Tyne and Wear Metro (TWM) system in the North East of England. This is to shed light on the potential use of land value capture methods for subsequent extensions. Whilst there has been substantial international research into transport related land value capture methods, this tends to take place in atypical capital cities with buoyant land markets and/or entire transport systems. This is reflected in England, where research is less frequent in major conurbations outside of Central London, which are more typical of urban areas in this country. In response, the intention is to shed new light on this situation by updating historical research into the impact of the TWM. Its primary focus is the longitudinal performance of the 2002 Sunderland Metro Extension (SME). This historical appraisal of impact is significant because it is important to understand when and how much uplift is generated. This in turn helps to evidence any justifications for subsequent extensions and funding via Land Value Capture. This study uses a novel time based analysis to quantify differences in property prices before, immediately after and fifteen years after the Sunderland Metro Extension (SME) was constructed. The original results show that property values increased immediately after the extension becomes operational, though no significant results were found 15 years later. Highlights: Land value impact in sub-optimal locations. Land value uplift appears to occur immediately after construction. Findings suggest that land value capture instruments should target capture immediately after construction of light rail extensions in sub-optimal locations.